Binary Gender in Yogyakarta Panji Masks: A Visual Semiotic Study - Wijaya, Yasin Surya; Subiyantoro, Slamet; Mulyanto (Mudra Jurnal Seni Budaya, 2025)
This study aims to explore the aesthetic values of binary gender (femininity and masculinity) within the visual structure of Yogyakarta Panji masks through the lens of semiotics. The research employs a descriptive qualitative approach with a single case study. The object of the study is the Yogyakarta Panji mask, whose visual structure is analysed to uncover symbols that indicate femininity and masculinity values. Data sources include informants, places, events, and documents/archives collected through in-depth interviews, participatory observations, and content analysis. The validity of the data is tested using data source triangulation and informant review techniques. Data analysis is conducted using the flow model of analysis, which involves data reduction, data display, and verification. The results indicate that the visual structure of Yogyakarta Panji masks, when examined through a semiotic framework, contains signs/symbols and values of femininity and masculinity. These values of masculinity and femininity are also embedded in and have been transformed into various cultural artifacts within the context of Javanese culture. The findings highlight that Panji masks not only reflect aesthetic expressions but also serve as cultural signifiers that preserve, communicate, and reinforce traditional Javanese perspectives on gender.